Pengaruh Daya Tarik Produk Dan Daya Tarik Promosi Terhadap Keputusan Pembelian Roti Boy di Kota Banda Aceh - Aida Fitri; Fani Sartika; Nara Pristiwa (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This study aims to determine the effect of product attractiveness and promotional attractiveness on purchasing decisions for boy bread in Banda Aceh City. The method used in this study is a quantitative method which aims to determine the effect or relationship between two or more variables in a study. The number of samples in this study were 96 respondents. The sampling technique used for data collection was carried out by means of nonprobability sampling using accidental sampling technique. Research data was collected through a list of questions / questionnaires and documentation studies. Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) are intended to determine the effect of the independent variable on the dependent variable at the 95% confidence level (α = 0.05). The results showed that simultaneously product attractiveness and promotional appeal influenced boy bread in Banda Aceh City. Then partially the attractiveness of the product and the attractiveness of the promotion affect the boy's bread in the city of Banda Aceh. So, the implications in this study are product attractiveness and promotional attractiveness that can influence consumers to purchase boy bread in Banda Aceh City.